Administrative Requirements and Prospects for Universal NDCs in Emerging Economies - Palacios, Robert (World Bank, Washington, DC, 2019)
Many public policies are impossible to implement without adequate administrative systems in place. This is true for modern pension schemes and in particular, notional defined contribution (NDC) schemes. Today these systems must be digital yet most pension systems predate computerization and must find a way to bridge past and present. The shift from defined benefit (DB) to NDC brings particular challenges in recordkeeping. This paper briefly reviews the administrative requirements of NDCs and offers a simple checklist for countries considering this type of reform. The last section describes a universal NDC scheme that harnesses the modern digital infrastructure that may allow developing countries to overcome the limitations of traditional contributory systems and their reliance on payroll taxes.